Test of the Anti-Inflammatory Effectiveness of Ethanol Extract of Cat's Whiskers Leaves (Orthisiphon Aristatus) on Paw Edema in Male Mice (Mus Musculus) - Pranata, Chandra; Darmirani, Yosi; Limbing, Reida (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Cat's whisker leaves contain secondary metabolite compounds, flavonoids and essential oils. The chemical compounds contained in cat's whisker leaves have antioxidant, antibacterial, anti-inflammatory and antifungal properties. Flavonoids are known to function as anti-inflammatories by inhibiting pro-inflammatory enzymes, namely by blocking cyclooxygenase or lipoxygenase, can influence cellular signaling pathways such as NF-kB which can inhibit the migration of inflammatory cells to areas of inflammation. Objective: to test the anti-inflammatory effectiveness of ethanol extract of cat's whisker leaves in-vivo. Method: Anti-inflammatory effectiveness testing was carried out on male mice (Mus musculus) by inducing edema on the soles of their feet using 0.1 ml of 1% carrageenan. This research was an experimental study with 5 treatments and 5 replications. The parameters observed were edema volume, edema percentage, and edema inhibition percentage. Edema volume measurements were taken every 60 minutes for 6 hours. The results of measuring the volume of edema were used to calculate the percentage of edema, which was then used to calculate the percentage of edema inhibition. Data on the percentage of edema inhibition were statistically analyzed using the One Way ANOVA test. Result: the results of statistical tests showed significant differences in data on the percentage of edema inhibition and the percentage of edema between treatment groups showing p<0.05. From the results of the percentage of edema inhibition, it shows that cat's whisker leaf extract with a concentration of 15% has the best anti-inflammatory effect, namely inhibition of 88.42% is the concentration with the optimum dose.